2020
DOI: 10.3389/fpsyg.2020.02213
|View full text |Cite
|
Sign up to set email alerts
|

Does the Relation Between Humor Styles and Subjective Well-Being Vary Across Culture and Age? A Meta-Analysis

Abstract: An earlier review (Schneider et al., 2018) examined the connection between humor styles and mental health. The present article supplements and extends Schneider et al.'s review by surveying a broader concept, subjective well-being (SWB), and investigating the moderating effects of culture and age. To this end, we collected data from 85 studies, with 27,562 participants of varying ages and cultures. Meta-analysis results indicate that affiliative and self-enhancing humor enhances SWB, whereas aggressive and sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(22 citation statements)
references
References 68 publications
(126 reference statements)
5
15
0
Order By: Relevance
“…Subsequently, we performed a second study to assess the associations among those self-efficacy dimensions and wellbeing across genders and different ages. We did not expect gender or age to substantially modify the relationships between self-efficacy beliefs and wellbeing, in accordance with previous findings concerning humor, positive memories and wellbeing ( Jiang et al, 2020 ). However, we cannot rule out that the perceived abilities in the three domains examined may have a slightly different relevance at different stages of life.…”
Section: Introductionsupporting
confidence: 91%
“…Subsequently, we performed a second study to assess the associations among those self-efficacy dimensions and wellbeing across genders and different ages. We did not expect gender or age to substantially modify the relationships between self-efficacy beliefs and wellbeing, in accordance with previous findings concerning humor, positive memories and wellbeing ( Jiang et al, 2020 ). However, we cannot rule out that the perceived abilities in the three domains examined may have a slightly different relevance at different stages of life.…”
Section: Introductionsupporting
confidence: 91%
“…Such discrepancies could be attributed to cultural differences in humor perception and usage. More specifically, it seems that individuals coming from collectivistic countries diverge from those from individualistic cultures such that they tend to evaluate humor as an undesirable trait and a poor coping strategy (Jiang et al, 2020). Further, the intercorrelations among the humor styles were higher (range: .23–.48).…”
Section: Discussionmentioning
confidence: 99%
“…They also revealed that self-defeating humor had the opposite pattern of relationships with wellbeing, and that aggressive humor style seems to be unrelated to these psychological outcomes. Recent meta-analytic extensions of these findings mostly align with these relationships considering various indices of mental health and subjective wellbeing as well as potential sociodemographic and cultural moderating effects (Jiang et al, 2020 ; Schneider et al, 2018 ). However, there are mixed results about the benefits of laughing at oneself in certain contexts, which suggests a potential positive side of self-defeating humor (e.g., Heintz & Ruch, 2018 1 ).…”
Section: Introductionmentioning
confidence: 76%